Civic Participation And Public Spaces: A Key Factor For Sustainable Tourism In Historic Cities - Zwan, Martin van der (Journal of Tourism, Sustainability and Well-being, 2016)
Attractive public spaces are crucial for tourism. After all, most tourists that visit a city, experience it by foot and increasingly by bicycle. Public spaces have to meet a few minimum requirements. If not, tourists will feel uncomfortable. For instance; a lot of rubbish and graffiti, worn out and damaged street furniture can cause a feeling of unsafety. Attractive public spaces are the ones that invite tourists to stay a bit longer than strictly necessary and sit down and relax. Some of these spaces are quit and green, others more vibrant, well dimensioned and furbished. In this paper I describe a method for defining and measuring the quality of public space and also for predicting the conclusion tourists may draw based on this; “will I revisit this place or not ?” In some cities inhabitants, local shop owners and local institutions voluntarily take the initiative to upgrade the quality of public spaces or even act as ‘city hosts’ to welcome visitors. These kinds of civic participation help to provide the unique experience many tourists are looking for.